2020
DOI: 10.1111/jgh.15070
|View full text |Cite
|
Sign up to set email alerts
|

The impact of deep convolutional neural network‐based artificial intelligence on colonoscopy outcomes: A systematic review with meta‐analysis

Abstract: The authors declare no conflict of interest. No human subjects/animals were involved in this systematic review and meta-analysis. Author contribution: Muhammad Aziz planned and conducted the study, collected and interpreted the data, conducted the statistical analysis, and drafted the manuscript. Rawish Fatima collected the data, interpreted the data, and drafted the manuscript. Dong Charles interpreted the data and drafted the manuscript. Wade Lee-Smith created the search strategy and collected the data, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 29 publications
3
52
0
1
Order By: Relevance
“…A recent meta-analysis focused on diagnostic performance of AI systems but not on direct comparison with HD colonoscopy for ADR [15] . Few other meta-analyses have recently been published highlighting similar findings as this study [ [20] , [21] , [22] ]. However, this study differs in the reporting of expanded pooled rates of colonoscopy parameters including the scope withdrawal time.…”
Section: Discussionsupporting
confidence: 88%
“…A recent meta-analysis focused on diagnostic performance of AI systems but not on direct comparison with HD colonoscopy for ADR [15] . Few other meta-analyses have recently been published highlighting similar findings as this study [ [20] , [21] , [22] ]. However, this study differs in the reporting of expanded pooled rates of colonoscopy parameters including the scope withdrawal time.…”
Section: Discussionsupporting
confidence: 88%
“…A recent study 12 found that AI methods working with 2 D colonoscopy images produced a high rate of false positives and produced miss rates comparable to experienced practitioners. The existence of false positives was also noted in 11 as an issue encountered with the AI method studied.…”
Section: Discussionmentioning
confidence: 92%
“…In the next stage of development, the system can employ AI and deep learning algorithms to further improve polyp detection. The availability of both 3 D and 2 D data as inputs to the AI, as opposed to only the traditional 2 D image data used in previously studied systems 10 11 , is expected to eliminate problems associated with the lack of strong features common in colonoscopy images, and thus improve the accuracy of operation. A recent study 12 found that AI methods working with 2 D colonoscopy images produced a high rate of false positives and produced miss rates comparable to experienced practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Current efforts are directed to increase the ADR for endoscopists by using numerous interventions (electronic chromoendoscopy, add-on devices, antispasmodic medications, multiple observers, water-aided methods, second forward exam or retroflexion in right colon, artificial intelligence) 7 8 9 10 11 12 13 . Two such add-on devices used in recent times are Endocuff (ECU) and Endocuff Vision (ECV) (Arc Medical Design, Leeds, UK) 14 .…”
Section: Introductionmentioning
confidence: 99%